ON THE CIVIL-LEGAL LIABILITY IN THE SPHERE OF PRODUCTS QUALITY PROVISION - A. S. Panova (Russian Journal of Economics and Law)
The article is devoted to the topical issues of the legal provision of products quality. The civil-legal liability of the producers (executives, sellers) in the sphere of the products quality provision is viewed.